Pengaruh Citra Merek terhadap Minat Beli Minuman Berenergi - Didit Darmawan; Naila Septiana Camelia (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The global consumption of energy drinks is currently faced with a paradox between the demand for instant performance enhancement and concerns regarding health risks. This study aims to analyze the strategic role of brand image in stimulating consumer purchase intention amidst this perceptual dilemma. Employing a qualitative approach through a literature review method, this research synthesizes findings from nine empirical studies published between 2019 and 2024. The analysis reveals that brand image consistently exerts a positive and significant influence on the escalation of purchase intention. Within a marketing framework, brand image functions as a risk mitigation instrument and a signal of trust capable of constructing positive consumer attitudes. These findings validate the Theory of Planned Behavior (TPB), where a strong brand identity triggers the psychological drive to perform a purchase. Practically, this study concludes that the effectiveness of energy drink marketing strategies highly depends on building an authentic and responsible brand image to foster public trust and loyalty amidst intense industrial competition.